Il rapporto fra teatro e letteratura in Carmelo Bene - Mancini, Leonardo (Mimesis Journal, 2017)
Which is the relationship between the literary works of Carmelo Bene and his theatre? Which the nature and which the value of his literary works, beyond his theatrical performances? A recent book by Simone Giorgino, L’ultimo trovatore. Le opere letterarie di Carmelo Bene analyses Bene’s literary works in prose and in poetry, including the late and unpublished poem, Leggenda. Using the instruments of literary criticism, Giorgino retraces the extraordinary rich influences, the styles and the innovative experimentations of Carmelo Bene’s writing, unfolding a new field of investigation still largely unexplored. The article moves from Giorgino’s analysis and discusses some of his thesis in order to call for a new unitary approach to Bene’s production, a production marked by a strong cultural commitment which still expects to be fully recognized. If it is not time to provide definitive answers, new perspectives lay open to the historiography on Carmelo Bene.